Determination of Tooth Length Variation Of Maxillary Canine - An Analytical Study - Naulakha, Deependra; Agrawal, Manish; Naulakha, Nootan (Journal of Nobel Medical College, 2015)
Aim: The Aim of this study was to assess the variation in anatomical tooth length of maxillary canine, irrespective of sex, in patient's presenting at NMCTH, Biratnagar, Nepal. Methodology: A total of 30 Endodontically treated maxillary canine were included in this study. Preoperative radiographs were taken initially for finding the canal length. Radiographic interpretation (IOPA X-rays) and mathematical calculation, proposed by Ingles and messing, were used to observe and measure the length of individual root canal for tooth length. An endodontic access was prepared and pulp tissue was extirpated. A working length radiograph was taken with a file in the canal and the radiographic working length was established. Results: This study revealed that the maximum, minimum and average tooth length of maxillary canine is 30mm, 18mm and 22.91 mm respectively. Conclusion: The result indicates that the study previously performed by different researchers and those given in the different textbook of endodontics showed that the tooth length is shorter than the caucasoid counterpart. DOI: http://dx.doi.org/10.3126/jonmc.v3i1.12236 Journal of Nobel Medical College Vol. 3, No.1 Issue 6, 2014, Page: 40-45